The Influence of Islamic Religious Education Implementation through the Sekolah-Ku Program on the Religious Attitudes of Children Diagnosed with Cancer - Muhammad Sulaiman; Yulius Tiranda; Noviana Mustapa; Amin Maghfuri; Satria Kharimul Qolbi (JIE (Journal of Islamic Education), 2025)
This study aims to examine the influence of the implementation and internalisation of Islamic Religious Education (IRE) values in the Sekolah-Ku program on the religious attitudes and spiritual resilience of children diagnosed with cancer. The research assumes that a contextual and empathetic approach to IRE contributes significantly to strengthening positive religious coping strategies and religious behaviour among the children. This quantitative field research involved 24 children as primary respondents, all actively participating in the Sekolah-Ku program during the data collection period. Data were obtained through participatory observation and unstructured interviews with the children, complemented by the Brief RCOPE questionnaire to measure religious coping strategies. Descriptive statistics and simple linear regression were applied to analyse the relationship between IRE implementation and the children's religious attitudes. The findings reveal a predominance of positive religious coping, reflected in children's frequent engagement in prayer, worship, and spiritual reflection to seek strength and comfort. Based on Glock and Stark's religiosity framework, the practice dimension was most prominent, followed by experience, ideological, and consequential dimensions. These results indicate that the IRE implementation in the Sekolah-Ku program effectively fosters the internalisation of religious values, encourages active religious practice, and supports children's spiritual resilience in serious health challenges. The study highlights the importance of adaptive, spiritually humanistic, and context-relevant religious education.